Boosting Vaccine-Elicited Respiratory Mucosal and Systemic COVID-19 Immunity in Mice With the Oral Lactobacillus plantarum - Xu, Jianqing; Ren, Zhihong; Cao, Kangli; Li, Xianping; Yang, Jing; Luo, Xuelian; Zhu, Lingyan; Wang, Xiangwei; Ding, Longfei; Liang, Junrong; Jin, Dong; Yuan, Tingting; et al. (Frontiers in Nutrition, 2021)
Boosting and prolonging SARS-CoV-2 vaccine elicited immunity is paramount for containing COVID-19 pandemic. Here we identified that a unique strain of Lactobacillus plantarum GUANKE (LPG) is capable to promote SARS-CoV-2 specific immune responses both in effective and memory phases through enhancing interferon pathway and suppressing apoptotic and inflammatory pathways. As early as in 1998, we observed that LPG is capable to boost memory immune responses 30 days post an oral vaccine of Shigella dysenteriae; Accordingly, LPG also promoted SARS-CoV-2 neutralization antibodies even 6 months after immunization in the absence of vaccine inoculation. Furthermore, when LPG applied immediately after SARS-CoV-2 vaccine inoculation, neutralization antibodies could be boosted for 10 folds in BAL and >2 folds in sera, T-cell responses could last and stabilize for a prolonged period both in BAL and spleen. Interestingly, oral application of LPG could mobilize immune responses among mucosal and systemic compartments, in particular, a gut-spleen and a gut-lung immune axes were observed. These data support that LPG could be applied in combination with SARS-CoV-2 vaccine to boost and prolong both effective and memory immune responses in mucosal and systemic compartments, thereby is likely to improve the efficacy of SARS-CoV-2 vaccine.